Caractérisation des chaînes de valeur et des marchés des cultures négligées et sous-utilisées à l’Ouest du Niger: Cas de patate douce, manioc, moringa, gombo, oseille et voandzou - Oumarou Haladou, Issoufou; De Falcis, Eleonora; Tietiambou, Fanta Reine Sheirita; Grazioli, Francesca; Borelli, Teresa; Naino Jika, Abdel Kader; Otieno, Gloria; Lochetti, Gaia; Acasto, Filippo; Ghione, Andrea; Pugliese, Patrizia; Bteich, Marie-Reine; et al. (African Journals Online (AJOL), 2024)
In West Africa, the alarming levels of food and nutrition insecurity compounded by poverty explain the failure of agricultural and food systems. Neglected and underutilized crops represent an opportunity to reverse this trend. This study focused on six crops including tubers, vegetables and legumes: cassava, sweet potato, moringa, Guinea sorrel, okra and bambara groundnut. The objective was to map and study the organization of actors, market characteristics, bottlenecks and opportunities. The methodology was based on Rapid Market Assessment (RMA). Between March and October 2022, interviews were carried out with 608 stakeholders and direct observations made. Data were used in a functional, economic and environmental analysis. Results showed that these crops provided a diversity of products including tubers for sweet potato and cassava, leaves for moringa and Guinea sorrel, fruits for okra and sorrel and seeds for bambara groundnut. Women dominated the production of bambara groundnut, okra and moringa. They monopolized the processing and men monopolized the marketing of all crops. Women's preferences were for moringa, sorrel and sweet potato. The market for these crops is promising due to the growing demand. Producers and processors benefit less in value chains. Taking into account opportunities and constraints, recommendations are proposed to improve the competitiveness and sustainability of these value chains.